Tax Policy for SMEs, Corruption Perception, and Firm Productivity in Indonesia: A Firm-Level Analysis - Bangun Canggih Wicara Putra (JIMF (Jurnal Ilmiah Manajemen Forkamma), 2022)
This study aims to assess the impact of a policy change in presumptive tax schemes and corruption on firm performance in Indonesia. The central government has enacted a new presumptive tax regulation targeting small and medium enterprises (SMEs) started in 2013. The policy intends to attract small businesses to pay income tax and promote formalization. Additionally, we also assess the impact of corruption compared to the effect of taxation, on firm productivity. Taking advantage of the reliable panel data from the World Bank Enterprise Survey Indonesia in the years 2009 and 2015, along with fixed-effect regression models, we find that the presumptive tax scheme does not significantly have an impact on firm productivity. This result may be explained by the formalization approach. In addition, it is confirmed that corruption is negatively and significantly affects firm productivity. This study also affirms several studies that corruption has a greater impact, compared to taxation, on firm productivity.